The SAGE handbook of criminological research methods - Gadd, David, 1975-; Karstedt, Susanne; Messner, Steven F., 1951- (Los Angeles, [Calif.] ; London : SAGE, 2012)
Looking at both the techniques and logic of inquiry surrounding methods used in criminological research, this progressive handbook brings together work from internationally renowned experts to provide readers with an important resource on the application of methods.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Criminology -- Research -- Methodology